The Influence of Infotainment Content, Remunerative Content, and Relational Content, on Purchase Intention Through Customer Engagement on Skincare Products on Social Media - Wulandari, Rikha; Puspitaloka Mahadewi, Erlina (International Journal of Science, Technology & Management, 2026)
This study aims to analyze the influence of infotainment content, remunerative content, and relational content on purchase intention through customer engagement for Scarlett Whitening skincare products on TikTok social media. The development of the skincare industry in Indonesia has increased competition between brands, requiring companies to optimize their digital marketing strategies through social media. One important factor in digital marketing is selecting the type of content that can build consumer engagement and drive purchase intention. This study used a quantitative approach with a survey method. Data was collected through distributing online questionnaires to 254 respondents who were Scarlett Whitening consumers in the Greater Jakarta area. The sampling technique used purposive sampling with the criteria of respondents aged 18–35 years and having purchased Scarlett Whitening products. Data analysis was carried out using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the help of SmartPLS 4.0 software. The results showed that infotainment content, remunerative content, and relational content had a significant effect on customer engagement. Furthermore, customer engagement has proven to have a significant effect on purchase intention. Testing the indirect effect shows that customer engagement mediates the relationship between infotainment content and relational content on purchase intention, but not the effect of remunerative content. This finding suggests that educational, entertaining, and relational content are more effective in building consumer engagement and driving purchase intention than incentive-based promotional content.